2014
DOI: 10.1111/cch.12161
|View full text |Cite
|
Sign up to set email alerts
|

‘They're not witches. …’ Young children and their parents' perceptions and experiences of Child and Adolescent Mental Health Services

Abstract: Children were able to provide potentially useful opinions of CAMHS. In a time of limited resources it is imperative that the voices of children and their parents are acknowledged in order to improve accessibility and experiences within CAMHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Young people in mental health services were concerned that PROMs might be used to narrow access to care; e.g., ‘If I tick ‘much worse’ then I don’t know if [that means] “I don’t need this service”, I don’t know, I’m very confused,’ (Young Person 4, 14, CAMHS). What is safe to reveal with PROMs may reflect a general fear of the unknown that children and their parents report when first attending CAMHS (Bone et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Young people in mental health services were concerned that PROMs might be used to narrow access to care; e.g., ‘If I tick ‘much worse’ then I don’t know if [that means] “I don’t need this service”, I don’t know, I’m very confused,’ (Young Person 4, 14, CAMHS). What is safe to reveal with PROMs may reflect a general fear of the unknown that children and their parents report when first attending CAMHS (Bone et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Active participation from young people, indeed from children, is paramount in influencing decisions on their care (United Nations, 2014). Several studies have shown that, when engaged and involved in a developmentally appropriate and sensitive way, even young children can formulate recommendations based on their experiences of psychosocial interventions and services (Bone et al, 2015). In this study, young people responded positively to the participatory research method of participants negotiating their answers in small groups rather than having individual interviews.…”
Section: Resultsmentioning
confidence: 82%
“…These scales have been suitable for children as young as 4 years old [34,35]. Additionally, emotion cards have been used in the hospital context to investigate experiences of children [36]. Since the digital survey tool was designed to be understandable to children as young as 4 years of age, we used emojis for informative and unambiguous visuals (see Table 1).…”
Section: The Digital Survey Toolmentioning
confidence: 99%
“…The design of the contents for the digital survey tool utilised earlier research on subjects like children's pain, anxiety measurements and emotions [26,29,34,36,[42][43][44][45]. Many of the previous studies used observer-based anxiety scales [18,25,26], such as the Modified Yale Preoperative Anxiety Scale (mYPAS), but some used subjective reporting, such as the Faces Pain Scale and Visual Analogical Scales (VAS) [29].…”
Section: Digital Survey Tool For Measuring Px and Its Evaluationmentioning
confidence: 99%